Ranking of Injection Biochar for Slag Foaming Applications in Steelmaking - DiGiovanni, Christopher; Li, Delin; Ng, Ka Wing; Huang, Xianai (Metals (Basel ), 2023)
The electric arc furnace (EAF) has the potential to significantly contribute to the decarbonization of the iron and steel industry. However, during EAF steelmaking, carbon still needs to be injected into the molten slag to initiate slag foaming, which is beneficial to the energy efficiency and protection of the furnace. To move away from fossil carbon, biocarbon has gained attention as an injection carbon agent. In this study, two biochar candidates were added to the molten slag layer of an induction furnace for steel melting, to simulate EAF steelmaking conditions. The resultant slag foaming height was measured, and a ranking in comparison to two fossil carbon candidates was developed. The results indicate that the injection biochar sample, in the form of a bio-briquette, has a considerable degree of slag foaming capacity. More work is ongoing to develop a standardized testing methodology of ranking various injection biochar candidates for their suitability and qualification for use on a larger scale.